2014
DOI: 10.1164/rccm.201306-1043oc
|View full text |Cite
|
Sign up to set email alerts
|

Aging Mesenchymal Stem Cells Fail to Protect Because of Impaired Migration and Antiinflammatory Response

Abstract: Taken together, the decreased expression of cytokine and chemokine receptors in aged B-MSCs compromises their protective role by perturbing the potential of B-MSCs to become activated and mobilize to the site of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 77 publications
2
131
0
Order By: Relevance
“…MSC treatment was beneficial only in aged mice (8-12 mo of age). Age affects various MSC functions, including expression and secretion of soluble factors important in recovery from lung injury (20). Aged animals show lower expression of genes involved in cell activation and migration and of cytokine receptors (e.g., TNFR1 and TNFR2) and chemokine receptors (CCR7, CX3CR1, and CXCR5) involved in MSC migration and chemotaxis (21).…”
Section: Discussionmentioning
confidence: 99%
“…MSC treatment was beneficial only in aged mice (8-12 mo of age). Age affects various MSC functions, including expression and secretion of soluble factors important in recovery from lung injury (20). Aged animals show lower expression of genes involved in cell activation and migration and of cytokine receptors (e.g., TNFR1 and TNFR2) and chemokine receptors (CCR7, CX3CR1, and CXCR5) involved in MSC migration and chemotaxis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dysfunction of other potential progenitor cell types, such as mesenchymal stromal cells (MSCs), has been associated with reduced repair capacity in a murine post-pneumectomy model [121]. BUSTOS et al [122] found diminished anti-inflammatory potential of bone marrow-derived MSCs from old mice. [20].…”
Section: Stem Cell Exhaustionmentioning
confidence: 99%
“…13 Researchers also probably do not fully appreciate the inherent diff erences between MSCs cultured from diff erent donors 82 and are only beginning to appreciate how age might aff ect MSC function. 83 Finally, we remain unable to answer defi nitively basic mechanistic questions, such as how MSCs have a therapeutic eff ect on non-pulmonary tissue when given intravenously. MSCs become trapped in the lung after intravenous administration, yet have benefi cial eff ects in traumatic brain injury and myocardial infarction (supporting the presence of secreted paracrine factors).…”
Section: Mitochondrial Transfermentioning
confidence: 99%